APPLICATIONS OF NANOPARTICLES IN THE DIAGNOSIS AND TREATMENT OF LUPUS NEPHRITIS - Pereira, Maiara Eduarda de Souza; Silva, Tialy Vitória Santos; da Silva, Maria Victoria Patrício; da Silva Júnior, Braziliano Miguel; de Lima, Camilla Albertina Dantas; Garcia, Paula Sandrin (Seven Editora, 2026)
Lupus nephritis (LN) is a complication of systemic lupus erythematosus (SLE) characterized by renal inflammation and potential progression to chronic kidney disease. The gold standard diagnosis is renal biopsy, an invasive and costly method, while conventional treatment is based on the use of immunosuppressants and glucocorticoids, associated with adverse effects and difficulties in therapeutic adherence. This review aimed to analyze the diagnostic methods and pharmacological interventions available for patients with LN, with an emphasis on nanoparticle (NP)-based strategies. The included studies demonstrated that different types of NPs (inorganic, polymeric, mineral, lipid, mesoporous, and exosomal) are being investigated for both the diagnosis and treatment of LN. In diagnosis, approaches such as gold NP-enhanced Raman spectroscopy, immunochromatographic tests for ALCAM detection, and theranostic nanoprobes capable of acting in imaging modalities such as magnetic resonance imaging and photoacoustic imaging were described. In treatment, targeted delivery systems for anti-inflammatory drugs, improved renal biodistribution, and reduced systemic toxicity were highlighted. Overall, NPs demonstrated potential to improve therapeutic and diagnostic strategies for lupus nephritis, although most studies are still experimental, indicating the need for further investigations. Literature review indicates that nanoparticles represent a promising strategy for the diagnosis and treatment of lupus nephritis, with potential for more specific and less toxic therapies and less invasive diagnostic methods, although they still depend on validation by clinical studies in humans.